A critical assessment of comparative advantages - Dvoskin, Ariel (2020)
Literature on international trade agrees that comparative advantages (CA) regulate the pattern of trade across countries. What is not usually stressed is that, for this to be possible, CA must be identified ex-ante by some ranking of international competitiveness. Otherwise, they become a tautology: countries are said to possess CA in those sectors that have managed to become internationally competitive. In this work, we show that when there is production of capital goods, in particular of imported means of production, and even under a zero profit rate: (a) the ranking of industries on the basis of autarky comparative costs may not be a good predictor of CA; (b) no ranking of industries exists, in general. The overall conclusion of the article is that CA cannot explain the pattern of trade and, therefore, an alternative explanation must be searched for.